Data to model risks for recolonizing wolves in Scandinavia through the integration of territory presence and human-driven mortalities - Mariano R. Recio; Barbara Zimmermann; Camilla Wikenros; Andreas Zetterberg; Petter Wabakken; Håkan Sand (Data in Brief, 2018)
This dataset article describes the data and sources used to model risks for the recolonizing wolf (Canis lupus) in Sweden and Norway in the article “Integrated spatially-explicit models predict pervasive risks to recolonizing wolves in Scandinavia from human-driven mortality” (Recio et al., 2018). Presences on wolf territories were used to model the potential distribution of the species. Presences of human-driven mortalities including traffic collisions, culling (protective/defensive, and licensed hunting), and illegal killing (i.e. poaching) were used to model predictions on the distribution of these mortalities. Sources for the independent variables used for the models are also described.